Say my name [book with audioplayer] - Ho, Joanna (Findaway World, LLC, 2023)
"New York Times bestselling author Joanna Ho, of Eyes That Kiss in the Corners, creates a meaningful and diverse picture book about how names define us. Names reveal generational ties and histories, weaving an intricate tale of the past. Names--and correctly saying them--are important. Each one carries the hopes, dreams, and traditions of those who came before us. Six children connect with the reader and proudly celebrate their names and backgrounds: Hé Xiao-Guang, Of a Kivaha Tupoumalohi, Bijan Hosseini, Nizhoni Yazzie, Xóchitl Luna, and Akosua Acheampong. These captivating kids of Chinese, Tongan, Persian, Navajo, Mexican, and Ghanaian descent also honor their ancestors and cultural histories. Joanna Ho's lyrical story, with gorgeous illustrations by Khoa Le, explains how saying a person's name is the only way we can truly know another."